From Host Heme To Iron: The Expanding Spectrum of Heme Degrading Enzymes Used by Pathogenic Bacteria - Lyles, Kristin V.; Eichenbaum, Zehava (Frontiers in Cellular and Infection Microbiology, 2018)
Iron is an essential nutrient for many bacteria. Since the metal is highly sequestered in host tissues, bound predominantly to heme, pathogenic bacteria often take advantage of heme uptake and degradation mechanisms to acquire iron during infection. The most common mechanism of releasing iron from heme is through oxidative degradation by heme oxygenases (HOs). In addition, an increasing number of proteins that belong to two distinct structural families have been implicated in aerobic heme catabolism. Finally, an enzyme that degrades heme anaerobically was recently uncovered, further expanding the mechanisms for bacterial heme degradation. In this analysis, we cover the spectrum and recent advances in heme degradation by infectious bacteria. We briefly explain heme oxidation by the two groups of recognized HOs to ground readers before focusing on two new types of proteins that are reported to be involved in utilization of heme iron. We discuss the structure and enzymatic function of proteins representing these groups, their biological context, and how they are regulated to provide a more complete look at their cellular role.